Integrating the SDG into university teaching: an application in human resources subjects - Mora-Valentín, Eva-María; Huertas-Valdivia, Irene; García-Moreno, Marta-Beatriz (Working papers on operations management, 2024)
The aim of this paper is to propose different initiatives to integrate the SDG into university education. To do so, firstly, some theoretical questions about the SDG and education are addressed. In addition, a review is made of previous research that has incorporated the SDG into university teaching. Finally, four activities are proposed that combine various teaching methodologies, as well as digital resources to facilitate the integration of the SDG in Human Resources subjects. Our proposal constitutes a guide to help teachers who want to incorpo-rate the SDG in subjects related to the management and administration of people.